Agrobacterium-mediated transient MaFT expression in mulberry (Morus alba L.) leaves - Wu, S.; Yang, X.; Liu, L.; Jiang, T.; Wu, H.; Su, Chao; Qian, Y.; Jiao, F. (2015)
© 2015 Japan Society for Bioscience, Biotechnology, and Agrochemistry. To optimize Agrobacterium-mediated transient transformation assay in mulberry (Morus alba L.), various infiltration methods, Agrobacterium tumefaciens (A. tumefaciens) strains, and bacterial concentrations were tested in mulberry seedlings. Compared with LBA4404, GV3101 harboring pBE2133 plasmids presented stronger GUS signals at 3 days post infiltration using syringe. Recombinant plasmids pBE2133:GFP and pBE2133:GFP: MaFT were successfully constructed. Transient expression of MaFT:GFP protein was found in leaves, petiole (cross section), and shoot apical meristem (SAM) of mulberry according to the GFP signal. Moreover, MaFT:GFP mRNA was also detected in leaves and SAM via RT-PCR and qRT-PCR. An efficient transient transformation system could be achieved in mulberry seedlings by syringe using A. tumefaciens GV3101 at the OD 600 of 0.5. The movement of MaFT expression from leaves to SAM might trigger the precocious flowering of mulberry.